DESAIN SISTEM INFORMASI GEOGRAFIS DAERAH RAWAN BANJIR KABUPATEN JEMBER - Nugroho Setyo Wibowo; Dwi Putro Sarwo Setyohadi; Hariyono Rakhmad (Jurusan Teknologi Informasi Politeknik Negeri Jember, 2019)
Geographic information system flood prone areas Jember district is a system that can provide information on flood-prone areas in each district where the vulnerable areas are obtained based on the calculation of fuzzy Tsukamoto accordance with the provisions that have been determined, in addition to providing information prone areas can also provide information the health facilities and the events that preceded the flood. This system is implemented in the form of digital map information with the aim to further facilitate the delivery of information. The data used was obtained from BPBDs (Regional Disaster Management Agency) and BPEKAP (District Development Planning Agency) Jember are then processed into a system suitable and appropriate. At the end result of this system will display information about flood-prone areas, health facilities, as well as data that precedes the events that are implemented in the form of digital maps for easier delivery.